(untitled) (Research, Society and Development, 2021)
Objective: to build and validate an instrument to identify myofunctional and vocal changes in the elderly by primary care health professionals in the city of João Pessoa-PB. Methods: Methodological study, since it deals with the construction and validation of the content of the Guidance Guide. For the validation of the instrument, eight expert judges participated in the theme. Approved by the Research Ethics Committee of the Federal University of Paraíba, under opinion 2,190,153, it followed all ethical aspects of Resolution 466/2012. For data analysis, the Content Validity Index was used. Results: in the integrative literature review, nine articles continued, with the largest number of publications in 2015. The studies pointed out that there are vocal and oromyofunctional changes arising from senescence, namely: hoarse voice, tremor and decreased vocal amplitude; reduction in tonus and strength of the tongue and masticatory muscles. In the validation of the Guidance Guide, in terms of objectives, structure, presentation and relevance, a general average of the Content Validity Index of 0.90 was obtained. Thus, the judges participating in the research confirmed their approval of their applicability, with the proposed material being validated by them. Conclusion: it is expected that the instrument will provide health professionals with the facility to identify changes in voice and oromyofunctional motor skills in the elderly at an early stage, allowing them to make referrals to the speech therapist and damage to the health of the elderly.